Diversity changes of rhizosphere and endophytic bacteria in Allium senescens L. under drought stress and rewatering - Song, Xue; Li, Haotian; Fu, Chuhan; Li, Jiahong; Xiang, Jihong; Sun, Xuetong; Liu, Jielin; Qin, Ligang (Frontiers in Plant Science, 2025)
IntroductionDrought stress severely impacts plant productivity, particularly in non-cultivated species such as Allium senescens.L. However, the role of rhizosphere and endophytic bacterial communities in enhancing drought tolerance remains underexplored.MethodsWe used 16S rRNA amplicon sequencing to investigate microbial communities in the rhizosphere, roots, bulbs, and leaves of A. senescens under simulated drought conditions using PEG-6000 (CK, 5%, 15%, 25%) and post-rehydration recovery. Alpha and beta diversity, phylogenetic relationships, and functional predictions were analyzed.ResultsDrought stress reduced rhizosphere bacterial diversity by 42% but increased leaf diversity by 52%. The 15% PEG treatment marked a key threshold for community shifts. Streptomyces and Ralstonia were significantly enriched under drought, and functional predictions indicated their involvement in osmotic regulation and phytohormone synthesis. Post-rehydration partially restored microbial composition in aerial tissues but not in the rhizosphere.DiscussionThese findings suggest that drought induces niche-specific microbial adaptations and that bacterial community structure plays a critical role in drought resilience. This study provides insights into plant-microbe interactions and offers a basis for developing microbial strategies to improve drought tolerance in Allium species.